2018
DOI: 10.1111/are.13851
|View full text |Cite
|
Sign up to set email alerts
|

The impact of different rearing condition on gilthead seabream welfare: Dissolved oxygen levels and stocking densities

Abstract: Aquaculture's success highly depends on a controlled rapid growth of organisms with minimal costs associated. Growth and welfare of reared organisms are affected by physical, chemical, and biological parameters. Following factors can be highlighted as crucial: density, pH, salinity, temperature, dissolved oxygen (DO), and nutrients (nitrogen, phosphorus, etc.). Relationship between fish density and oxygen's optimum levels is essential for designing the performance of each species. Furthermore, it is also neces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 48 publications
1
13
0
2
Order By: Relevance
“…Araújo‐Luna et al. (2018) reported that the most frequent damage in gills documented was hyperplasia and cellular anomalies (degeneration and necrosis), with congestion in the secondary lamellae. Moreover, the potential impact of yucca on the protection of fish tissues from the harmful influences of hypoxia is not well documented.…”
Section: Discussionmentioning
confidence: 99%
“…Araújo‐Luna et al. (2018) reported that the most frequent damage in gills documented was hyperplasia and cellular anomalies (degeneration and necrosis), with congestion in the secondary lamellae. Moreover, the potential impact of yucca on the protection of fish tissues from the harmful influences of hypoxia is not well documented.…”
Section: Discussionmentioning
confidence: 99%
“…The first sign of a mismatch between O 2 supply and demand is the reduction of appetite, varying the O 2 threshold level for maximal feed intake in Atlantic salmon ( Salmo salar ) and gilthead sea bream ( Sparus aurata ) between 40% and 75% saturation within the range of temperature tolerance [ 17 , 18 ]. This threshold level is decreased at high stocking densities [ 19 , 20 , 21 ], probably due to the unbalanced production and scavenging of reactive O 2 species (ROS) [ 22 ]. However, acclimation to one stressor can also improve the capacity to cope with another critical co-occurring stressor, and warm acclimation improves the hypoxia tolerance in Atlantic killifish ( Fundulus heteroclitus ) [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Arctic charr ( Salvelinus alpinus ) or meager ( Argyrosomus regius ) kept at high stocking densities evidenced a better growth performance than fish reared at low densities as long as water quality was preserved (Jørgensen et al, 1993; Millán-Cubillo et al, 2016). The impact of crowding stress can also be minimized when O 2 levels are not below LOS (Ruer et al, 1987; Araújo-Luna et al, 2018). Unraveling the combined effects of hypoxia and high rearing density are, thereby, crucial to warrant welfare during intensive fish farming.…”
Section: Introductionmentioning
confidence: 99%